Społeczne uwarunkowania zdrowia i choroby człowieka - Ziarkowski, Eugeniusz (Wydział Prawa i Administracji UAM, 1984)
A rapid development of studies of sociologists of medicine on the one hand and the traditional domination of medicine by natural sciences on the other, induce for a more profound reflection of the essence of two closely interrelated processes of health and disease of a man. Its thorough study calls for enrichement of present knowledge of health problems of individuals and society with a produce of social sciences and for defining the participation of sociologists in studies on origins of disease process. Following a thesis of social nature of human being and abandoning naturalistic interpretation of individual and collective phenomena effects a demonstration of all limitations of medical and natural interpretation of sickness and health but also proves a thesis of socio- natural substance of subject of medical studies. Therefore, learning of the whole conditioning of a genesis of morbid process cannot do without knowledge and concepts of social sciences. In consequence human malady can be defined as a socio-natural process set by historically and culturally changing conditions of social existence which describe relations entered by an individual throughout personal life with natural and social environment. In this aspect a research program on sociogenesis of disease contains examination of three spheres of social reality: 1) influence of social process on human ontogenesis, what eqauls to defining social premises of such formation of features of organism which either by themselves or conditioned by individuals functioning in society and nature predispose to morbid process, 2) learning of that aspect of social process in which individual or group intervention in the world of nature effects such relations between individual and environment which would cause morbid process, 3) learning of those phenomena and social processes which are forming personality and social conditions of human existence and of those which introduce a man into such relations 'with social environment that a morbid process is developed on account of particular features of individual's organism and-or personality. The research program on social conditioning of disease is a counterproposal to earlier formulated sociological theories of disease.
Social conditioning of health and disease of a man